SEZ Counseling for Pregnant Women - Ananda Mustaqim, Teguh; Yulianti, Syami; Amorita, Yulia; Akbar, Rasyid; Gusti Iman Ramadhan, Satria; Rosita, Pera (Universitas Dehasen Bengkulu, 2025)
Malnutrition in pregnant women, particularly Chronic Energy Deficiency (CED), remains a serious issue in Indonesia. CED can lead to various health complications for both the mother and the fetus, such as prolonged labor, preterm birth, postpartum hemorrhage, and congenital anomalies. Education and counseling on the prevention of CED are crucial to enhance pregnant women's knowledge about its risks and prevention methods. This community service program was conducted by KKN students from Universitas Dehasen Bengkulu in Kesambe Lama Village, Curup Timur District, Rejang Lebong Regency. The program included observation, interviews, preparation of educational materials, and implementation of counseling sessions. The results showed an increase in participants' knowledge about CED, as well as their ability to explain the risks and prevention methods.